Pengaruh Rasio EWS dan RBC Terhadap Kinerja Keuangan Perusahaan Asuransi yang Terdaftar di BEI Tahun 2015-2019 - Suwarni, Karina; Ulupui, I Gusti Ketut Agung; Khairunnisa, Hera (LPPM Universitas Negeri Jakarta, 2023)
This study aims to analyze the influence of Risk Based Capital (RBC) variable and early warning system ratio on the financial performance of insurance companies. To achieve this objective, a quantitative analysis method was used, and secondary data in the form of financial reports from 14 insurance companies listed on the Indonesia Stock Exchange during the period of 2015-2019 were collected. In this study, the early warning system ratio was proxied by the claim ratio, commission ratio, and own retention ratio, while panel data regression analysis was used as the analytical technique. The results indicate that RBC has a significant influence on the financial performance of insurance companies, while the claim ratio, commission ratio, and own retention ratio have no significant effect on financial performance.